Return and volatility spillovers between the US, Japanese and Malaysian stock markets - Lida Nikmanesh,; Abu Hassan Shaari Mohd Nor,; Tamat Sarmidi,; Hawati Janor, (Penerbit Universiti Kebangsaan Malaysia, 2014)
The present study investigates the return and volatility spillover between the stock markets of the US, Japan and Malaysia using weekly data concerning the S&P 500, NIKKEI 225 and KLCI composite indices from January 1990 to May 2013. Employing a cross-correlation function method, the results show that a unidirectional causality-in-mean exists from the stock markets of the US and Japan to the Malaysian stock market. Malaysian stock returns immediately react to the shocks received from the stock markets of the US and Japan and the reaction continues for 12 weeks. The causality-in-variance test shows that the volatility of the Malaysian stock market is more affected by the US stock market than the Japanese stock market. Similarly, the variance-causality test shows that the speed of variance spillover from the US stock market to the Malaysian stock market is high; and is significant from the first week. The results from the present study are relevant for fund managers and investors when making investment decisions that involve the consideration of risk and return elements; for policy makers to monitor the financial market stability; and for hedgers to forecast risk and develop hedging strategies.